Pengaruh Likuiditas, Profitabilitas dan Solvabilitas terhadap Harga Saham: Studi Empiris pada Perusahaan Manufaktur di Bursa Efek Indonesia Periode 2019-2021 - Aji, Muhammad Kartiko; AC, Ali Mauludi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The following research is carried out as a step in testing the suitability of the hypothesis that the company's liquidity, profitability, and solvency have an impact on the high and low stock prices. the author will use the independent variables in the form of the current ratio, return on assets, and debt to equity ratio, while the dependent variable will use the stock price of a manufacturing company. The following research will involve a sample of manufacturing companies that have been listed and remain actively marketed on the Indonesia Stock Exchange (IDX) in the period 2019 to 2021. The population we have selected includes around 181 companies. We will use the simple random sampling method to select the sample, which involves random selection from the existing population. A total of 22 companies will be sampled in the following research. The multiple regression statistical method will be used to analyze the relationship between various variables in manufacturing companies and the dependent variable that is to be predicted in the following research. In this study, the results found that simultaneously, the liquidity ratio, profitability ratio and solvency ratio did not have a statistically significant effect on the prediction of stock prices in the capital market. In addition, statistically, the liquidity ratio, profitability ratio and solvency ratio partially do not show a significant effect on estimating the price of shares in the capital market on the Indonesia Stock Exchange (IDX). Keywords: Liquidity, Profitability, Solvency, Stock Price, Manufacturing.